Risk and prognosis of secondary malignant neoplasms after radiation therapy for bladder cancer: A large population-based cohort study - Chen, Ru; Zhan, Xiangpeng; Jiang, Haoxin; Liu, Yang; Jiang, Zhi; Jiang, Ming; Deng, Wen; Liu, Xiaoqiang; Chen, Guoxian; Fu, Bin (Frontiers in Oncology, 2022)
Objective To investigate the association between radiotherapy and the risk of second malignant neoplasm (SMN) development among patients with bladder cancer (BC). Overall survival (OS) is compared among patients developing SMN and without. Method We identified patients diagnosed with BC from the Surveillance, Epidemiology, and End Results (SEER) database. The development of an SMN is defined as any SMN occurring more than 5 years after the diagnosis of BC. The Fine-Gray competing risk regression is used to estimate the probability of SMN. The radiotherapy-associated risk (RR) for SMNs is assessed by Poisson regression. The Kaplan–Meier method was used to evaluate the OS of patients with SMNs. Propensity score matching (PSM) is performed. Results A total of 76575 BC patients are enrolled in our study. The probability of SMNs in the radiotherapy cohort is statistically higher than in the non-radiotherapy cohort. In competing risk regression analysis, radiotherapy is proven to be associated with a higher risk of SMN (Hazard ratio: 1.23; 95% CI: 1.102–1.368). The radiotherapy-associated risks significantly increase in the radiotherapy cohort (RR: 1.28; 95% CI: 1.14–1.43). In site-specific analysis, statistically significant results are observed in lung and bronchus (LAB) cancer and hematological malignancies. The OS rate in patients developing SMN is significantly lower than that among matched patients with primary BC. Conclusion Radiotherapy for BC is associated with SMN. Radiotherapy increases the risk of secondary low-dose area cancer development, including LAB cancer or hematological malignancies. Notably, this effect is not observed in the high-dose area involving pelvic tumors. Patients developing SMN showed poorer OS.